An Algorithmic Metaphysics of Self-Patterns - Beni, Majid D. (Frontiers in Psychology, 2020)
the paper draws some criteria from algorithmic complexity to demonstrate that the self (as initially described in Shaun Gallagher’s a pattern theory of self) is a composite, scattered, and patterned object. It also addresses the question of extendedness of the self-pattern. Based on the criteria drawn from algorithmic complexity, I argue that although the self-pattern possesses a genuinely extended aspect (and in this sense, the self-pattern is minimally extended) the self-pattern and its environment do not constitute a genuine composite object.